PaACL silencing accelerates flower senescence and changes the proteome to maintain metabolic homeostasis in Petunia hybrida. (4th May 2020) - Zhao, Huina; Zhong, Shiwei; Sang, Lina; Zhang, Xinyou; Chen, Zeyu; Wei's, Qian; Chen, Guoju; Liu, Juanxu; Yu, Yixun
Abstract: Cytosolic acetyl-CoA is an intermediate of the synthesis of most secondary metabolites and the source of acetyl for protein acetylation. The formation of cytosolic acetyl-CoA from citrate is catalysed by ATP-citrate lyase (ACL). However, the function of ACL in global metabolite synthesis and global protein acetylation is not well known. Here, four genes, PaACLA1, PaACLA2, PaACLB1, and PaACLB2, which encode the ACLA and ACLB subunits of ACL in Petunia axillaris, were identified as the same sequences in Petunia hybrida 'Ultra'. Silencing of PaACLA1-A2 and PaACLB1-B2 led to abnormal leaf and flower development, reduced total anthocyanin content, and accelerated flower senescence in petunia 'Ultra'. Metabolome and acetylome analysis revealed that PaACLB1-B2 silencing increased the content of many downstream metabolites of acetyl-CoA metabolism and the levels of acetylation of many proteins in petunia corollas. Mechanistically, the metabolic stress induced by reduction of acetyl-CoA in PaACL -silenced petunia corollas caused global and specific changes in the transcriptome, the proteome, and the acetylome, with the effect of maintaining metabolic homeostasis. In addition, the global proteome and acetylome were negatively correlated under acetyl-CoA deficiency. Together, our results suggest that ACL acts as an important metabolic regulator that maintains metabolic homeostasis by promoting changes in the transcriptome, proteome. and acetylome. Abstract : PaACL silencing reduced anthocyanin contents, accelerated flower senescence, and changed the proteome and acetylome to maintain metabolic homeostasis in petunia